Strength of cylindrical butt joints bonded with epoxy adhesives under combined static or high-rate loading. (June 2016) - Murakami, S.; Sekiguchi, Y.; Sato, C.; Yokoi, E.; Furusawa, T.
Abstract: The influence of loading rates and the combined stress states of tension and shearing on the strength, strain, and absorbed energy of an adhesively bonded joint was experimentally investigated. Cylindrical butt joint specimens were prepared and strength tests were performed on the specimens with a servo-controlled hydraulic testing machine that combined tension and torsion loading. Two types of epoxy adhesives, ductile and brittle, were applied to the specimens. The tests were performed under a quasi-static condition of 6.67×10 −2  MPa/s and a high-rate loading condition of 1.00×10 3  MPa/s. The results of the combined loading tests showed that the states of the fractured surfaces were not affected by the loading rates. As for the ratio of tensile and shear loading, adhesive failure tended to partially occur when the ratio of shear loading was very high. The strength points for the specimens bonded with each adhesive were distributed in a stress plane of tension and shearing and could be fitted with a curve that was described by an equation with exponential parameters that were not influenced by the strain rate; however, other parameters that described the intercepts were influenced. The failure strains and absorbed energies for the brittle adhesive were slightly dependent on the strain rate, but this dependency was unclear for the ductile adhesive.